KAJIAN SEMIOTIK: INTERPRETASI PUISI KUROFUNE KARYA KINOSHITA MOKUTARO - Zaki Ainul Fadli (Universitas Diponegoro, 2015)
[The interpretation of Kinoshita Mokutaro’s Kurofune] This article discusses about the interpretation of poetry with semiotic approach. As the object of this study is one of Kinoshita Mokutaro’s poetries: Kurofune. Decoding the dramatic situation and connotation of a poetic text can be helpful for its interpretation. The dramatic situation of Kurofune will be discussed with semiothics theory from Riffaterre. In Riffaterre’s theory, poetry can be interpreted with heuristic and hermeneutic’s reading. The purpose of this article is to know the poetry’s implied meaning. The terms of Black Ships(Kurofune) commonly refer to the American steam-powered warships led by Commodore Matthew Calbraith Perry which first arrived in Uraga in 1853. But as the result of the analysis, the term kurofune can be also read as the end of shakoku and the beginning of new era called the Meiji Restoration.